Chemosensor development of cu2+ recognition using 1,5-diphenylcarbazone: optimization, cosmo-RS and DFT studies - Ismail, Nur Hakimah; Yunoh, Ros Shuhada; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya (2018)
The sensitive and selective chemosensor for copper (II) ions (Cu2+) was successfully optimized using the 1,5-diphenylthiocarbazone (DPT) compound. Results showed that Dimethyl Sulfoxide (DMSO) in a 9:1 ratio with a co-solvent at a pH 3 was the optimum condition for DPT to act as chemosensor of Cu2+ recognition. The DPT chemosensor did not encounter any interference from other metal ions, including Fe3+, Ag+, Cr3+, Pb2+, Cu2+, Mg2+, Cd2+, Zn2+, K+, Ni2+ and Co2+ . The presence of Cu2+ led to an absorption peak at 658 nm, where the colour changed from cantaloupe to grey-green color indicating the interaction by the formation of the DPT-Cu complex in 2:1 stoichiometry. The theoretical σ-profile calculation using conductor-like screening model for real solvents (COSMO-RS) showed the compatibility of DPT with the DMSO solvent through hydrogen bonding. In the density functional theory (DFT) calculations, the formation energy of DPT and DPT-Cu were -1113.79645660 a.u. and -2435.71832681 a.u., respectively. Under optimal conditions, a detection limit of 1.47 ppm for the DPT chemosensor for Cu2+ recognition can compete with the atomic absorption spectroscopy (AAS) value of 1.50 ppm. The preliminary results show that DPT was able to provide less expensive, more portable and convenient chemosensor for Cu2+ recognition in aqueous medium, as compared to AAS.